Increasing performance of rotary ultrasonic motor through stator modification - F. R. M., Romlay (2013)
This thesis concerns with the performance of the travelling wave ultrasonic motor (TWUSM). The performance of TWUSM is mainly constraint by the quality of the piezoceramic material, the electrical driving signal synchronisation and optimization, the heat dissipation system during the operation and the stator-roto interface designed. One of the factors in the stator-rotor interface design is the deflection amplifier mechanism. Under travelling wave electrical excitation, the piezoceramic layer of the stator vibrates by expanding and compressing. The amplitude of the vibration is amplified by the metal attached on the top of the piezoceramic layer. The metal vibration is in contact with the rotor and through a frictional layer, torque is generated and the rotor rotates. This mechanism of transferring the piezoceramic vibration to the rotor motion is called deflection amplifier. Current TWUSM utilises the comb-teeth structure as the deflection amplifier. One of the factors that influence the deflection amplifier is the position of the stator neutral axis to the contact surface of the stator. Thus, the objective of this thesis is to modify the design of the comb-teeth stator so that the neutral axis position is further distance from the stator top contact surface. The proposed solution is to remove selected mass element from the combteeth structure. Modelling and simulation of the proposed concept were carried out under Marc Mentat FEM software utilising Shinsei USR60 as the chosen TWUSM. Results from the modal, harmonic, transient and stress analyses indicate that the modified comb-teeth stator increases the position of the neutral axis from the stator top surface. Due to the neutral axis shifting, simulation results also confirm that the stator speed increases for the modified stator. To observe the performance of the modified stator, experiments were conducted using Shinsei USR60 as the test platform. One set of Shinsei USR60 motor was modified by drilling hole to the comb-teeth structure. Results from experiments confirm that the motor with the modified stator produced better speed, torque and power consumption.